From vulnerability to promise perspectives on Ricur from women philosophers - Arrien, Sophie-Jan 1971-; Contreras Tasso, Beatriz (Lexington Books, 2025)
"This book brings together ten women philosophers to examine Paul Ricur's philosophical anthropology, focusing on the embodied dimension of existence, to reveal its ontological and ethical significance. The contributors examine Ricur's work in a variety of contexts, such as freedom and recognition, love and consent, and our inescapable finitude"--
Keywords: Philosophical anthropology; Civilization / Philosophy; Women philosophers; Ricur, Paul; Anthropologie philosophique; Civilisation / Philosophie; Femmes philosophes; philosophical anthropology; philosophers